The Implications of Spillover for the Design of Monetary Policy: An Empirical Analysis of Income and Price Determination in Nonclearing Markets - Ferguson, J. David; Hart, William R. (American Economic Review, 1985)
Macroeconomics is currently dominated by two competing frameworks of analysis through which the adherents of each attempt to explain the paths of aggregate economic variables and address the design of policy. One, the market-clearing or equilibrium approach to business cycles, is most prominently associated with the work of Robert Lucas (1972), Thomas Sargent (1976), Sargent and Neil Wallace (1976), and Robert Barro (1976). The other employs the nonmarket-clearing framework made fashionable by the work of Stanley Fischer (1977), Edmund Phelps and John Taylor (1977), and Taylor (1979). Despite the apparent theoretical superiority of the market-clearing approach (i.e., the realization of all perceived gains from trade), the non-market-clearing approach continues to dominate analysis of macroeconomic fluctuations. This is explained partly by the failure of equilibrium macroeconomic models to fare well empirically and partly by the successful incorporation of the notion of rational expectations into non-market-clearing models. The current spirit of the non-market-clearing approach emphasizes forward-looking (rational) contractual wage setting in which wages are set to clear labor markets. Shortrun rigidity of the wage contract, however, prevents instantaneous clearing of the labor market in the face of economic disturbances, and as such, becomes a source of short-run deviations in aggregate variables from their natural rates. One aspect of the non-market-clearing approach emphasized early in the literature by Don Patinkin (1952) is the notion of spillover-a situation in which buyers facing markets that clear only gradually are unable to purchase all they intend of a good at a given price, and therefore, redirect part of their unspent income to another market. The micro foundations for spillover in a model of nonclearing markets were provided in a seminal paper by Herschel Grossman (1969) in which Patinkin's concept of spillover was synthesized with the Takashi Negishi-Frank Hahn (1962) nontatonnement transaction process and Robert Clower's (1965) dual-decision hypothesis. And yet, despite these contributions, the concept of spillover has been largely ignored in the majority of current genre non-market-clearing models. In two companion pieces (1980, 1983), we formally incorporated Grossman's (1969, 1971) work into a generalized macro model and used dynamic simulations to derive the implications of market spillover for income and interest rate determination in a short-run environment of gradual adjustment of demand and expectations and nonclearing markets. Our results suggested that spillover provides an additional potential explanation for short-run quantity adjustments and, as such, is important for the short-run design of monetary policy. However, two considerations serve to temper our earlier results: 1) the models employed were fixed price; and 2) the models were not estimated. Therefore, the question still remained whether spillover mattered empirically. This paper answers this question by specifying and estimating a generalized macroeconomic model that not only incorporates the concept of spillover into a framework of nonclearing financial and real markets, but also includes a supply side to allow for flexi*Associate Professors, Miami University, Oxford, OH 45056. We thank James Dunlevy, William Hutchinson, and Nicholas Noble for their generous help on this paper. And special thanks are due Bill McKinstry for his continuous support and encouragement. We alone are responsible for any errors.